Roles of hypothalamic neuropeptide gene expression in body mass regulation in Eothenomys miletus (Mammalia: Rodentia: Cricetidae). Issue 1 (1st January 2017) - Wanlong, Z.; Di, Z.; Dongmin, H.; Guang, Y.
Abstract: To investigate the roles of hypothalamic neuropeptide expression in body mass regulation in Eothenomys miletus, body mass, food intake, serum leptin levels and hypothalamic neuropeptide expression were measured in seasonal-acclimatized and lab-acclimated animals. The results showed that body mass, body fat mass and food intake showed seasonal variations. Serum leptin levels also appeared similar seasonal variation, showing a similar trend to body fat mass. Expression of hypothalamic neuropeptide Y (NPY) and agouti-related protein (AgRP) levels showed significant seasonal differences, while pro-opiomelanocortin (POMC) and cocaine- and amphetamine-regulated transcript (CART) expression showed no significant differences among seasons. Leptin had negative correlation with NPY and AgRP expression, positive correlation with POMC and CART expression among seasons. Cold and food restriction reduced body mass, body fat mass and serum leptin levels, and increased NPY and AgRP expression, but decreased POMC and CART expression. Photoperiods had no significant effect on these characters. Leptin was positively correlated with body fat mass, CART and POMC, and negatively correlated with NPY and AgRP under different temperatures, photoperiods and food quantity acclimation. All of these results showed that E. miletus reduced body mass and body fat mass, and increased food intake to survive in winter under seasonal changes. Temperature and food resources were the key factors influencing the body mass and energy metabolism in E. miletus . Leptin may play an important role in regulating body mass and energy metabolism by acting on hypothalamic neuropeptide expression in E. miletus .